A numerical study on fracture-plugging behaviour of granular lost circulation materials - Gui Wang,; Xiaolin Pu, (Universiti Kebangsaan Malaysia, 2014)
A distinct element approach has been introduced for simulating the plugging performance of granular lost circulation materials (LCM) in a fracture. This approach solves the fully coupled fracture walls, fluid and particles system in an interactive environment. The effects of the particle shape, size distribution and concentration on the fracture-plugging performance of the granular LCM have been investigated using the three-dimensional particle flow code (PFC3D). The simulated results showed that the irregular granular LCM could plug a fracture width larger than the sieving granulation by single-particle bridging type. The particle size distribution (PSD) of LCM dominates the plugging depth and efficiency in a fracture and there exists an optimum concentration for maximum effect of LCM additives.